Access to finance in the Western Balkans - Isabella Moder; Niccolò Bonifai (European Central Bank (ECB), 2017)
Limited access to finance is one of the main obstacles for firms located in the Western Balkans and hampers economic growth as well as the transmission of monetary policy. The aim of this paper is to undertake an in-depth analysis of access to finance constraints in this region, where countries as EU candidates or potential candidates have a prospect of joining the European Union. Besides touching upon macroeconomic and banking sector indicators that influence access to finance, this paper empirically assesses firm-level factors that determine whether a firm operating in the Western Balkans is credit-constrained, both in actual and perceived terms. In line with the literature, the results suggest that size, age, location, being audited, having outstanding loans and expectations about future performance matter for actual credit availability. The econometric analysis is complemented by a review of the Western Balkan countries' Economic Reform Programmes, which indicate that financing constraints are tackled by most national authorities through specific policy measures, mostly for small and medium-sized enterprises.
Keywords: E22; G30; O16; 330; financing constraints; SMEs; economic development